UJI EFEK EKSTRAK N-HEKSANA DAUN BAWANG KUCAI (Allium tuberosum Rottl ex Spreng) TERHADAP KOLESTEROL TOTAL PADA TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR - ., Cynthia Oktora Dwiyana (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Garlic chives/kucai (Allium tuberosum Rotll ex Spreng)contain Allicin compound. The Allicin compound has an inhibitory effect forHMG-CoA reductase enzyme so that the cholesterol level was decreased.Objective: The research would investigate the effect of reduction totalcholesterol and effective dose of garlic chivesâ€™s n-hexane extract in malewistar rate compared with atorvastatin as possitive control. Method: Theresearch was a time series experiment. Twenty five wistar rat wasrandomly divided into 5 experimental group, negative control (CMC 1%),positive control (atorvastatin), dose IÂ (0,0225 g/200 gBW), dose II (0,045g/200 gBW), and dose III (0,09 g/200 gBW) that was induced by highcholestrol diet for 14 days. The resulting data is analyzed with One-wayAnova test continued with LSD Post Hoc testing. Result: Fromphytochemical testing result, garlic chives n-hexane extract containsteroid/terpenoid secondary metabolite. Statistical analysis showedsignificance difference between average cholestrol level from controlgroup (negative and positif) againts dose I group and dose II group(p<0,05) at day-42. The effective dose was 0,09 g/200 gBB Conclusion:N-hexane extract of garlic chives has total cholestrol reduction effect onwhite male wistar rat with effective dose at 0,09 g/200 gBW which showthe same effectivity with atorvastatin.Key Words: Allium tuberosum Rottl ex Spreng, n-hexane extract of garlicchives, high cholestrol diet, total cholestrol level lowering effect 1) Medical School, Faculty of Medicine, Universitas TanjungpuraPontianak, Kalimantan Barat 2) Pharmacy School, Faculty of Medicine, Universitas TanjungpuraPontianak, Kalimantan Barat 3) Departement of Biochemistry, Medical School, Faculty of Medicine,Universitas Tanjungpura Pontianak, Kalimantan Barat